2007
DOI: 10.1183/09031936.00126306
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of exudative pleural effusions based on multiple biological parameters

Abstract: Pleural effusion is a common complication of various diseases. Conventional methods are not always capable of establishing the cause of pleural effusion, so alternative tests are needed. The aim of this study was to explore means of discriminating between different pleural effusion groups, malignant, parapneumonic and tuberculous, based on the combined function of seven biological markers.Adenosine deaminase (ADA), interferon-c, C-reactive protein (CRP), carcinoembryonic antigen, interleukin-6, tumour necrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 34 publications
8
71
0
4
Order By: Relevance
“…We showed that a pleural fluid CRP level .80 mg?L -1 argues for the presence of a PPE (LR+ 7.4), whereas CRP levels ,20 mg?L -1 are a strong indicator against an infectious pleural effusion, whether of bacterial or mycobacterial nature (LR-0.22). Indeed, a number of studies provide support for the use of CRP as a diagnostic aid in tuberculous pleuritis; low pleural CRP levels (,30 mg?L -1 ) make this diagnosis unlikely while being more indicative of a malignancy in patients with exudates [8][9][10]. In addition, our findings complement the scarce previous literature on the application of CRP for identifying CPPE [11,12].…”
Section: Discriminating Ppe From Other Aetiologiessupporting
confidence: 70%
“…We showed that a pleural fluid CRP level .80 mg?L -1 argues for the presence of a PPE (LR+ 7.4), whereas CRP levels ,20 mg?L -1 are a strong indicator against an infectious pleural effusion, whether of bacterial or mycobacterial nature (LR-0.22). Indeed, a number of studies provide support for the use of CRP as a diagnostic aid in tuberculous pleuritis; low pleural CRP levels (,30 mg?L -1 ) make this diagnosis unlikely while being more indicative of a malignancy in patients with exudates [8][9][10]. In addition, our findings complement the scarce previous literature on the application of CRP for identifying CPPE [11,12].…”
Section: Discriminating Ppe From Other Aetiologiessupporting
confidence: 70%
“…They concluded the combination of ADA and CRP levels might be sufficient in discriminating the three different groups of pleural effusion, tubercular, malignant and PPE. 21 In the present study, in most cases of tuberculous pleural effusion the ADA levels were >40U/L and CRP levels >2mg/dl, in PPE the ADA levels were <40 U/L (except empyema cases) and CRP levels >6mg/dl, where as in both malignant and transudative pleural effusions the ADA levels were <40U/L (except a mesothelioma case) and CRP levels <2mg/dl. The present study is in accordance with findings of Daniil ZD et al 21 CONCLUSION: Both pleural fluid ADA and CRP testing are minimally invasive, inexpensive and efficacious method of differentiating pleural effusion.…”
Section: Discussionsupporting
confidence: 47%
“…However, few studies, being retrospective and small, have directly compared the accuracy of both imaging techniques in this setting. 2,3 Results indicate that either CT does not provide additional useful information beyond what has already been seen on TUS, 2 or the latter outperforms the former in the identification of complicated PPE (CPPE) defined by pleural fluid analysis (respective likelihood ratio positive of 6.92 and 2.20).…”
Section: From the Authormentioning
confidence: 96%
“…In addition, a combined usage of thoracic ultrasound (TUS) HI and a simple biomarker such as adenosine deaminase or C-reactive protein may facilitate an early classification of PPEs. 3 Despite the fact that chest CT offers a variety of useful information regarding pleural pathology that might contribute to the differentiation among PPEs, concerns regarding the cost and ionizing radiation are important considerations in daily clinical practice. Though CT is preferred for the detection of loculations, septations may only be implied.…”
mentioning
confidence: 99%